PENGARUH INTENSITAS RESEARCH AND DEVELOPMENT DAN THIN CAPITALIZATION TERHADAP TAX AVOIDANCE DENGAN MODERASI KOMITE AUDIT - Rasya Ameilya Zein; Rokhmania, Nur'aini; Erida Herlina (Jurnal Bisnis Terapan, 2026)
This study aims to analyze the influence of research and development (R&D) intensity and thin capitalization on tax avoidance, as well as the role of the audit committee as a moderating variable. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The research data was obtained from the companies' annual financial reports and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS software. The results indicate that R&D intensity affects tax avoidance, as does thin capitalization. Furthermore, the audit committee is proven to moderate the relationship between R&D intensity and tax avoidance, as well as the relationship between thin capitalization and tax avoidance. These findings contribute theoretically by enriching the literature on tax avoidance and providing practical insights for policymakers in designing more effective regulations. Additionally, the results of this study can help companies develop more transparent and accountable tax strategies.